ANALYSIS OF THE APPLICATION OF THE HALAL PRODUCT GUARANTEE SYSTEM ON MSME’S CAK GISI MEATBALLS, PEDAGANGAN, GRESIK - Ramadany, Nyolanda; Pratiwi, Viera Nu’riza (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
The Indonesian state has an obligation to implement the Halal Assurance System to ensure that the products produced are safe and halal, this is because the majority of the Indonesian population is Muslim, so business actors are required to have halal certification. Business actors in Indonesia reach 99.99% who are MSME business actors, but MSME actors in Indonesia have not yet fully implemented a halal assurance system that can guarantee halalness in their products, following cases were found in Indonesia in 2018 namely the positive meatball case using pork, so that SMEs in Indonesia need to implement a halal product guarantee system.This research is a descriptive qualitative research that is carried out by in-depth interviews and observations to fill out the checklist for conformity of the SJPH based on the BPJPH. This data checklist was carried out 2 times: before and after education. The instruments of this research are interviews and the SJPH conformity checklist, including: Commitments and Responsibilities, Materials, Halal Product Processes, Products, Monitoring & Evaluation. From the results of the research on several components of the SJPH, there are still discrepancies between the implementation of the MSME Cak Gisi location and the regulations made by BPJPH, the discrepancy is due to a lack of knowledge and awareness of MSME actors, the absence of a halal policy and halal supervisor, and no special training regarding SJPH. , as well as unwillingness to implement SJPH due to time constraints and considered impractical.